Meditations for overcoming life's stresses and strains open your heart and let your bloodstream flow freely - Siegel, Bernie S. (Carson, CA : Hay Home, 2004)
Dr. Siegel presents a peaceful, relaxing journey to release stress and connect with the true self, and to help regulate one's heart and blood pressure.
Contents on sound disk : Stress & the inner self meditation (30:00) - Heart & blood pressure meditation (23:00).
Narration, Bernie S. Siegel ; music, Robert Gass.
Keywords: Meditation music; Psychotherapy; Stress (Physiology)